(untitled) (ARQUISUR Revista, 2024)
Extension Award - Category A The works nominated for the ARQUISUR Extension Award are those projects –whether they are in progress or executed-, whose impact can be verified, carried out by disciplinary and interdisciplinary teams made up of students, teachers and/or graduates, in order to allow the integration, articulation and strengthening of the different disciplinary areas of the Universities and developing various transferences to society of the scientific, technological and cultural knowledge, as a feedback system for academic activity. Category A contains works that are related to the community and are developed within the framework of Curricular Activities during a specific academic period of time (month-s, quarter-s, four-months period-s, etc.)